THE EFFECT OF WORK COMPETENCY, WORK ENVIRONMENT AND JOB SATISFACTION ON THE PERFORMANCE OF EMPLOYEES OF THE LEGAL BUREAU OF THE REGIONAL SECRETARIAT OF NORTH SUMATRA PROVINCE - Lina; M. Rizki; Feni Tiona Br Simangunsong; Goval Sunici Conan Sinaga; Tri Siwi Agustina (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Legal Bureau of the Regional Secretariat of North Sumatra Province, A government unit office functions as the main support unit in local government legal affairs, The establishment of this bureau began with the need to handle various legal issues related to local government policies, including the preparation of regional regulations, providing legal opinions, and government defense in legal cases. The total population in this study was 45 employees from the Legal Bureau of the North Sumatra Governor's Office, and saturated samples were used to analyze the results. The results showed that work competence influenced the results of 0.002<0.05 The estimated tvalue of 3.284 shows this, exceeding the critical value of 2.021. Positively and significantly employee performance, the work environment influences the results of 0.026<0.05 indicating that the work environment influences several aspects of employee performance. As evidence, note the calculated tvalue of 2.302>ttable 2.021. positively and significantly employee performance, as well as job satisfaction influences The pvalue of 0.003<0.05 indicates that job satisfaction influences employee performance. The fact that the predicted tvalue of 3.143 exceeds the ttable value of 2.021 positively and significantly affects employee performance. Overall, Job Competence, Work Environment, and Job Satisfaction have a positive and significant influence on Employee Performance.